Assessment of country implementation of the WHO global health sector strategy on sexually transmitted infections (2016-2021). - Melanie M Taylor; Teodora Wi; Antonio Gerbase; Soe Soe Thwin; Sami Gottlieb; Maria Theresa Babovic; Daniel Low-Beer; Monica Alonso; Maeve B Mello; Naoko Ishikawa; Anne Brink; Joumana Hermez; et al. (PLoS ONE)
Background In 2016, WHO launched the Global Health Sector Strategy on STIs, 2016-2021 (GHSS) to provide guidance and benchmarks for country achievement by 2020 and four global targets for achievement by 2030. Methods A country survey jointly developed by experienced technical personnel at WHO Headquarters (HQ) and WHO regional offices was reviewed and distributed by WHO regional advisors to 194 WHO Member States in September-March 2020. The survey sought to assess implementation and prioritization of STI policy, surveillance, service delivery, commodity availability, and surveillance based on targets of the GHSS. Results A majority (58%, 112/194) of countries returned a completed survey reflecting current (2019) STI activities. The regions with the highest survey completion rates were South-East Asia Region (91%, 10/11), Region of the Americas (71%, 25/35) and Western Pacific Region (67%, 18/27). Having a national STI strategy was reported by 64% (72/112) and performing STI surveillance activities by 88% (97/110) of reporting countries. Availability of STI services within primary health clinics was reported by 88% of countries (99/112); within HIV clinics by 92% (103/112), and within reproductive health services by 85% (95/112). Existence of a national strategy to eliminate mother-to-child transmission of HIV and syphilis (EMTCT) was reported by 70% of countries (78/112). Antimicrobial resistance (AMR) monitoring for gonococcal infection (gonorrhoea) was reported by 64% (57/89) of reporting countries with this laboratory capacity. Inclusion of HPV vaccine for young women in the national immunization schedule was reported by 59% (65/110) and availability of cervical cancer screening was reported by 91% (95/104). Stockouts of STI medicines, primarily benzathine penicillin, within the prior four years were reported by 34% (37/110) of countries. Conclusions Mechanisms to support improvements to STI service delivery through national-level policy, commitment, programming and surveillance are needed to operationalize, accelerate and monitor progress towards achievement of the 2030 global STI strategy targets.